2012
DOI: 10.1002/hep.25938
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide adenine dinucleotide phosphate oxidase in experimental liver fibrosis: GKT137831 as a novel potential therapeutic agent

Abstract: Background & Aims NADPH oxidase (NOX) generates reactive oxygen species (ROS) in hepatic stellate cells (HSCs) during liver fibrosis. In response to fibrogenic agonists, such as angiotensin II (Ang II), the NOX1 components form an active complex including Rac1. Superoxide dismutase 1 (SOD1) interacts with the NOX-Rac1 complex to stimulate NOX activity. NOX4 is also induced in activated HSCs/myofibroblast by increased gene expression. Here, we investigate the role of an enhanced activity SOD1 G37R mutation (SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
250
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 279 publications
(261 citation statements)
references
References 51 publications
(91 reference statements)
10
250
0
1
Order By: Relevance
“…It has been shown to provide endorgan protective effects, albeit in the liver. 22,52 Importantly, in our study, treatment of diabetic ApoE 2 / 2 mice with GKT137831 mimicked the effects of Nox4 deletion on glomerular injury, albuminuria, ROS production, ECM accumulation, and macrophage infiltration. Thus, the renoprotective effects of GKT137831 are likely to be mediated by Nox4 rather than Nox1 inhibition.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been shown to provide endorgan protective effects, albeit in the liver. 22,52 Importantly, in our study, treatment of diabetic ApoE 2 / 2 mice with GKT137831 mimicked the effects of Nox4 deletion on glomerular injury, albuminuria, ROS production, ECM accumulation, and macrophage infiltration. Thus, the renoprotective effects of GKT137831 are likely to be mediated by Nox4 rather than Nox1 inhibition.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, the genetic deletion studies were complemented by a pharmacologic intervention study using the currently most specific Nox inhibitor, GKT137831. 22 Key findings in the in vivo studies were confirmed in vitro using human podocytes.…”
mentioning
confidence: 70%
“…These results suggest that bone loss could be attenuated by the inhibition of NOX4. NOX4 inhibitors 13 are currently in preclinical testing and could represent a novel class of future osteoporosis drugs. Although several different anti-osteoporotic agents have been developed such as the gold standard bisphosphonates, there is a need for effective new treatment strategies.…”
Section: -10mentioning
confidence: 99%
“…GKT137831 is a weak inhibitor of Nox2 in cell-free assays and did not significantly inhibit neutrophil oxidative burst. GKT137831 had no radical scavenging or antioxidant activity and did not show significant in vitro offtarget inhibition of 170 different proteins, indicating high Nox specificity (21,22).…”
mentioning
confidence: 98%
“…The current study used GKT137831, a recently described pyrazolopyridinedione derivative that inhibits Nox4 and Nox1 (21), to further examine the role of Nox4 in hypoxia-induced alterations in pulmonary vascular cell proliferation and PH. GKT137831 [2-(2-…”
mentioning
confidence: 99%